2006
DOI: 10.7589/0090-3558-42.4.849
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Blood from Big Brown Bats (Eptesicus fuscus) in the Field with and without Anesthesia: Impacts on Survival

Abstract: ABSTRACT:Blood was collected from wild big brown bats (Eptesicus fuscus) with and without anesthesia in Fort Collins, Colorado in 2004 to assess the impacts of these procedures on shortterm survival and 1-yr return rates. Short-term survival and 1-yr return rates after release were passively monitored using PIT tag detection hoops placed at selected buildings. Comparison of 14-day maximum likelihood survival estimates from bats not bled (142 adult females, 62 volant juveniles), and bats sampled for blood with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Blood was obtained through interfemoral vessels as described by Wimsatt et al [44], except that anesthesia was discontinued because there was no difference in survival between anesthetized, unanaesthetized, and unbled bats [49]. Oropharyngeal secretions of bats were sampled at the laboratory using cotton-tipped swabs inserted into 0.5 ml of BA-1 medium (Minimal Essential Medium with Hanks’ balanced salt solution containing 0.05 M Tris buffer at pH 7.6, 1% Bovine Serum Albumin, 0.35 g/L of Sodium bicarbonate, 50 mg/L Gentamicin, and 2.5 mg/L Amphotericin B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood was obtained through interfemoral vessels as described by Wimsatt et al [44], except that anesthesia was discontinued because there was no difference in survival between anesthetized, unanaesthetized, and unbled bats [49]. Oropharyngeal secretions of bats were sampled at the laboratory using cotton-tipped swabs inserted into 0.5 ml of BA-1 medium (Minimal Essential Medium with Hanks’ balanced salt solution containing 0.05 M Tris buffer at pH 7.6, 1% Bovine Serum Albumin, 0.35 g/L of Sodium bicarbonate, 50 mg/L Gentamicin, and 2.5 mg/L Amphotericin B).…”
Section: Methodsmentioning
confidence: 99%
“…We based the survival estimates on encounters of tagged bats with PIT tag readers in fixed positions at entrances of five roosts monitored from 2001–2005 [46]. Survival was calculated using Program Mark with differences between the seropositive and negative groups determined by χ 2 goodness-of-fit tests in Program Release Test 1 [49], [65]. A more detailed multi-model analysis of factors influencing adult survival that does not include serological status was previously published [27].…”
Section: Methodsmentioning
confidence: 99%
“…Sampling and handling techniques for bats were described in detail by Wimsatt et al (2005) and Ellison et al (2006). Bats captured at roosts were selected for sampling at random, whereas bats captured over water were sampled ad libitum.…”
Section: Study Areas and Bat Capturementioning
confidence: 99%
“…The method of inserting a needle into the subcutaneous space is similar with both techniques with the biggest difference being that PIT tag needles are generally much larger (12 gauge). Research conducted on the effects of using needles on small mammals have found no long-term injuries or decreases in survival rate associated with the insertion of PIT tags (Neubaum et al 2005;Ellison et al 2006).…”
Section: F I N E -N E E D L E a D I P O S E A S P I R A T I O Nmentioning
confidence: 99%